Empirical Study Of Students' Acceptance Of Learning Objects - Lau, Siong Hoe (2008)
This study examined the underlying factors and causal relationships that determine learners' behavioural intentions to use learning objects in the context of higher education. Based on the literature review of several theories and models in Information Science (IS) discipline, which can serve as a framework to formulate the preliminary Learning Object Acceptance Model (LOAM) for evaluating the acceptance of learning objects among higher education students have been identified.